Reliability of ultrasonography to detect inflammatory lesions and structural damage in juvenile idiopathic arthritis - Lucio Ventura-Ríos; Enrique Faugier; Laura Barzola; L. B. De la Cruz-Becerra; Guadalupe Sánchez-Bringas; Andrés Rodríguez García; Rocío Maldonado; Johannes Roth; Cristina Hernández-Díaz (BMC, 2018)
Abstract Background Musculoskeletal Ultrasonography (MSUS) is an important tool for the clinical assessment in Juvenile Idiopathic Arthritis (JIA). The objective of this study was to evaluate the reliability of MSUS to detect elementary lesions: synovitis, tenosynovitis, cartilage damage and bone erosions in the wrist and metacarpal (MCP) joints of patients with JIA. Methods Thirty children in various subgroups of JIA according to ILAR criteria, were included in this cross-sectional study. Clinical data including painful, swollen and limited joints were recorded. Five rheumatologist ultrasonographers, blinded to the clinical evaluation, evaluated the presence of elementary lesions in the wrist and MCP 2 and 3 joints bilaterally. The synovitis was graded in B-Mode and Power Doppler (PD). In addition to descriptive statistics intra- and inter-observer reliability was calculated using Cohen's kappa according to Landis and Koch. Results US detected more synovitis than the clinical examination (62% vs 28%, 30% vs 23% and 22% vs 17% in the wrist, second and third MCP joints respectively). The intra-observer concordance for synovitis in all joints was excellent in B-Mode (k 0.84 .63-1.0 p = 0.001), except for MCP 2, where it was good (0.61, IC 95% .34-89, p = 0.001). For both modalities (PD, B-Mode) tenosynovitis, cartilage damage and bone erosions it was also excellent. Regarding synovitis grading the concordance was excellent for all grades (0.83-1.0, IC 95% 0.51.1.0, p = 0.001), except for grade 1 where it was good (0.61, IC 95% 0.43-.83, p = 0.001). Reliability inter-observer for grayscale synovitis (0.67-0.95, IC 95% 0.67-1.0, p = 0.001), tenosynovitis grayscale (0.89, IC 95% 0.78-0.99, p.001), damage cartilage (0.89, IC 95% 0.78-0.99, p = 0.001), PD (0.66, IC 95% 0.39-1.0, p = 0.001). The concordance for grading synovitis was excellent, but for grayscale grade 1 and 2 (.66, IC 95% .53-.74, p = 0.007) and PD grade 1 and 2 (0.63, IC 95% .58-.91, p = 004) was good. Conclusions The intra- and inter-observer reliability of MSUS for inflammatory and structural lesions is good to excellent for the wrist and MCP in patients with JIA.